HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG KESEHATAN REPRODUKSI REMAJA DAN POLA ASUH ORANG TUA DENGAN SIKAP REMAJA TENTANG SEKS BEBAS DI SMA N 1 TAWANGSARI SUKOHARJO - Oktiva, Yayuk Dwi; Muhlisin, Abi (Universitas Muhammadiyah Surakarta, 2010)
The progressive of Interaction among the existing adolescent hardly worrying of especially behavior of free sex is circle by adolescent. Some factors influencing behavior are the position of adolescent assuming behavior of free sex is development of era which must be followed. Some factor influencing adolescent position to free sex for example adolescent knowledge, pattern takes care of old fellow, milieu, etcetera. Purpose of this research are to known the correlation between adolescent knowledge about health of reproduction and pattern takes care of old fellow with adolescent position about free sex at student SMA N 1 Tawangsari Sukoharjo. This research is descriptive research of correlative that is explaining relation between two phenomenons that is adolescent knowledge about reproduction health; pattern takes care of adolescent old fellow and position about free sex. Research sample are 274 students at SMA N 1 Tawangsari Sukoharjo applies technique cluster random sampling. Data processing technique applies analytical technique Chi Square. Based on the result of research and solution, hence conclusion from this research is: (1) the knowledge about health of reproduction of student in SMA N 1 Tawangsari Sukoharjo most of good, (2) the pattern takes care of student old fellow in SMA N 1 Tawangsari Sukoharjo most of authoritative, (3) the adolescent position about free sex at student SMA N 1 Tawangsari Sukoharjo most of good, (4) there is relationship is being between adolescent knowledges about health of reproduction with adolescent position about free sex at student SMA N 1 Tawangsari Kabupaten Sukoharjo. So improvement of adolescent knowledge about reproduction health, hence adolescent position about free sex also increasingly good, and (5) there is low relationship between patterns takes care of old fellow with adolescent position about free sex at student SMA N 1 Tawangsari Kabupaten Sukoharjo. Result of research indicates that student having pattern to take care of authoritative to have position about free sex better than student having pattern to take care of permissive.